Para sobrevivir en la calle hay que tener miedo (2007)
ABSTRACT: To understand the meaning of fear and how to face it, from the participant point of view. Methodology: Ethnographic qualitative research was made with children living on the street in Medellin city from 2005 to 2007. It was an apply observation, interviews and ﬁeld book Technics. Results and Discussion: The fear on the street is based on the fear to the other one, to lose the beloved one, to aggression, to be killed, to the pain caused by injuries, to be a drug addict, to lose freedom and to AIDS. The fear has several meanings “Adrenalin” and “enemy”; the former allows the street people to run away and face some situations, and the latter paralyses and freezes them, so they can be caught, hurt or even killed. Conclusions: Fear is a survive strategy, which tries to change the enemy as fear into Adrenalin, to protect themselves, using strategies like psychological training.